Design and Build a Real-Time Based 3 Kg LPG Distribution Information System Using the Laravel Framework at PT. Tasya Gasindo - Yasmin Neylanda Pulungan; Meilita Tryana Sembiring; Juliza Hidayati (Formosa Journal of Computer and Information Science, 2026)
PT. Tasya Gasindo, an LPG 3 kg distribution agent in Medan, Indonesia, faced significant operational inefficiencies due to the absence of a real-time stock and demand monitoring system. Trucks frequently returned to the depot with unsold cylinders, causing queuing delays and Pertamina fines for unmet daily Delivery Order targets. This study designed and implemented a web-based distribution information system using the Laravel frame-work (MVC architecture, MySQL) providing real-time stock and demand data across 69 distribution bases. The descriptive-qualitative and software engineering approach included observation, interviews, and documentation. Black Box Testing covered 16 scenarios (all passed) with direct user evaluation. Average monthly residual cylinders decreased from 744 units (2022–2024) to 220 units in March–April 2025 a 70.4% reduction. The Fulfill-ment Rate improved from 99.20% to 99.74%, reducing estimated monthly Pertamina fines from Rp22.32 million to Rp6.60 million